الدور العلمي والديني لكل من الشيخين أحمد العبيدي (1888-1977م) والطاهر بن دومة (1918-1982م) - باوية, أميرة إكرام; مخاتري, سميرة (جامعة الوادي university of Eloued, 2022)
الملخص: يتناول موضوع هذه الدراسة " الدور العلمي والديني لكل من الشيخين أحمد العبيدي 1888م-1977م والطاهر بن دومة 1918م-1982م"، حيث كان لظهور الشخصيتين الدور الكبير في الجانب العلمي والديني، فنجد أحمد العبيدي الرجل العالم الفقيه الكريم والخلوق الذي كانت بداية عمله كمتطوع في بعض المساجد, وبفضل جده واجتهاده وطريقة إلقاءه أصبح إماما ومدرسا، يستفيد الناس من فتاويه وأحاديثه، وتخرج على يده العديد من الطلاب، كما كان مهتما بالتدريس الفقهي, حيث كان يركز على كل كبيرة وصغيرة، زد على ذلك بروزه ودوره الكبير في فض النزاعات وإصلاح ذات البين، وكان له منهجه الخاص في ذلك، أما الطاهر بن دومة الرجل الخير المتواضع المدافع عن رجال الدين فتمثل دوره في كونه من بين المثقفين الذين استعانت بهم الدولة لتلقين أجيال المدارس مبادئ اللغة العربية وقواعدها وتطوع هذا الأخير في إلقاء الدروس وكذا اعتكافه تعليم القرآن الكريم، وقد خصص جزء من بيته للتعلم وكذلك علم في المساجد دروس الوعظ والإرشاد والتوحيد، وقد تخرج على يده تلاميذ وحفظة القرآن ومعلمون، كما نجده أصلح المجتمع بمحاربته للآفات الاجتماعية، فاطلق عليه الحكيم وقد ترك لنا العديد من المؤلفات. Abstract: The subject of this study deals with the “scientific and religious role of the two Sheikhs Ahmed Al-Obaidi 1888-1977 CE and Taher Bin Douma 1918-1982 CE”, as the appearance of two such men had a great role in the scientific and religious aspect. In some mosques, thanks to his grandfather, his diligence and the way he delivered it, he became an imam and a teacher. People benefit from his fatwas and hadiths, and many students graduated from him. He was also interested in teaching jurisprudence, as he focused on everything big and small, in addition to his prominence and his great role in resolving disputes and reconciling matters. He had his own curriculum and authored many books in the arts of literature, grammar, jurisprudence and some poetic systems. As for Imam al-Taher bin Douma, the benevolent and humble man who defends the clergy, his role is represented in being among the intellectuals whom the state has used to indoctrinate the generations of schools with the principles and rules of the Arabic language. He taught in mosques lessons of preaching, guidance and monotheism, and students, memorizers of the Qur’an and teachers graduated from him. We also find him reforming society by fighting pests, as well as reforming the condition of young men and women, as well as families, so the wise called him and he left us many book Mots-clés : Richesse palmeraie, pays de Touggourt, colonialisme.
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: أحمد العبيدي، الطاهر بن دومة